STRATEGI PENGEMBANGAN AGRIBISNIS KOPI ROBUSTA DI KABUPATEN SOLOK - Hariance, Rika; Febriamansyah, Rudi; Tanjung, Faidil (Jurnal AGRISEP, 2016)
The purpose of this study is to formulate agribusiness development strategy of robusta coffee. By taking the area productian as a consideration, this study chose threeareas as the research site purposively which are Sub district Tigo Lurah, Pantai Cermin and X Koto Singkarak. The data for this this study were analized qualitatively by using SWOT and QSPM analysis. Based on SWOT and QSPM analysis, the main strategy indevelopment of  agribusiness robusta coffee is improving competitiveness through quality improvement of robusta coffe and its other processed products. Expectantly this strategy could overcome the main problem of agribusiness robusta coffe in Solok district such as low quality and low competitiveness of robusta coffe in this area. Moreover,  the alternatif policies that could be established based on the stategy above are (1) rehabilitating robusta coffe plantations in  order to increase the production, (2) replanting the unproductive robusta coffee trees, (3) planting the new robusta coffe trees, and (4) maintaining the quality by apllying the recommendation of cultivation technique and post production.